DEVELOPMENT OF VILLAGE TOURISM THROUGH RIVER WATER SPORTS IN WONODADI KULON VILLAGE, NGADIROJO SUB-DISTRICT, PACITAN DISTRICT: PENGEMBANGAN WISATA DESA MELALUI OLAHRAGA AIR SUNGAI di DESA WONODADI KULON KECAMATAN NGADIROJO KABUPATEN PACITAN - Indra Kusuma, Angga; Rentika Hadi, Santika; Hayati; Rangga Prastyana, Brahmana; Wahyono, Muhammad; Hanafi, Moh; Emir Rizkanto, Billy (Antis-publisher, 2024)
The potential that exists in each region is often not fully utilized, especially in relation to the development of village tourism, including in Wonodadi Kulon village, Ngadirojo District, Pacitan Regency, East Java Province. One of the village potentials that can be developed is village tourism based on river water sports. Through Community Service Program activities, it is hoped that existing resources can be optimized so that the village becomes a tourist village based on river water sports. The Community Service Program will be implemented from October to November 2023 in Wonodadi Kulon Village, Ngadirojo District, Pacitan Regency, East Java Province. The method used in community service program activities is based on the asset-based approach (ABA). The activity stages include field observations, drafting material requirements and implementation, licensing, implementation of service, evaluation, up to the final report. The general results of the activity were that training and mentoring activities related to the development of village tourism based on river water sports were carried out with 35 participants. Activity material includes introduction to river water sports, management, water sports facilities and infrastructure, prevention and first aid for accidents, as well as publication and marketing using social media. The conclusion from these activities is that the development of water sports-based village tourism can be carried out, including through training and mentoring activities, especially in Wonodadi Kulon Village, Ngadirojo District, Pacitan Regency, East Java Province